2019
DOI: 10.3390/su11061741
|View full text |Cite
|
Sign up to set email alerts
|

Daily Accessed Street Greenery and Housing Price: Measuring Economic Performance of Human-Scale Streetscapes via New Urban Data

Abstract: The protective effects of street greenery on ecological, psychological, and behavioral phenomena have been well recognized. Nevertheless, the potential economic effect of daily accessed street greenery, i.e., a human-scale and perceptual-oriented quality focusing on exposure to street greenery in people’s daily lives, has not been fully studied because a quantitative measuring of this human-scale indicator is hard to achieve. This study was an attempt in this direction with the help of new urban data and new a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 53 publications
4
60
0
Order By: Relevance
“…The reason why the HPR_DIS was chosen is that the distance from each neighborhood centroid to the Huangpu River notably affects residential housing prices. The housing prices decrease with the increase of the distance [30].…”
Section: Other Characteristicsmentioning
confidence: 93%
See 2 more Smart Citations
“…The reason why the HPR_DIS was chosen is that the distance from each neighborhood centroid to the Huangpu River notably affects residential housing prices. The housing prices decrease with the increase of the distance [30].…”
Section: Other Characteristicsmentioning
confidence: 93%
“…The rapid development of computer vision provides an efficient method for the information extraction of street view images. In this context, a great number of studies have been conducted to measure street-level green [27], estimate the spatiotemporal patterns of urban mobility [28], examine the relationship between street view and perceived safety [29] and assess the visual quality of urban environment [30] Therefore, in this study, street view data is used to evaluate the relationship between urban environmental elements and housing prices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely documented that the price of a property is influenced by the attributes of the property, such as gross floor area, age, transportation accessibility, and landscape view. The (traditional) hedonic pricing model is an extensively-adopted reveal-preference method for quantifying the contributions of various characteristics, from which utility is derived, to the prices of heterogeneous goods (e.g., properties) sold in a particular market [39][40][41][42][43][44]. The hedonic pricing model assumes that implicit prices (or hedonic prices) for each characteristic of a good can be decomposed into prices of a set of observable attributes [45] and estimated by observing purchasers' willingness to pay.…”
Section: Methodsmentioning
confidence: 99%
“…Zhou et al (2018) employed space syntax to analyse the street network evolution in ancient Beijing. Ye et al (2019) identified street greenery in the daily lives of city residents and examined its relationship with housing prices. Sheng, Yang, and Liu (2014) assessed consumer demands of the Wangfujing Area in Beijing (China) with the employment of space syntax.…”
Section: Introductionmentioning
confidence: 99%